2016
DOI: 10.3389/fpsyg.2015.02065
|View full text |Cite
|
Sign up to set email alerts
|

Not Just Being Lifted: Infants are Sensitive to Delay During a Pick-Up Routine

Abstract: In the present study we observed whether infants show online adjustments to the mother’s incipient action by looking at their sensitivity to changes as the pick-up unfolded. Twenty-three 3-month-old infants and their mothers were observed in the lab, where mothers were instructed (1) to pick-up their infants as they usually did (normal pick-up), and then (2) to delay the pick-up for 6 s after placing their hands on the infants’ waist (delayed pick-up). In both Normal and Delayed conditions infant’s body tensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
2
10
0
1
Order By: Relevance
“…Yet it does provide an interesting approach for looking into early participation and recognition of the global structure of routines by focusing on the individual steps of the peekaboo game and how the infants fit their behavior into these. In concert with the evidence suggesting that sequential structure affects early participation in interactions (Fantasia et al, 2015 ), it seems plausible that mothers who create more opportunities for their infants to take up their turn will have infants who participate more actively than other infants.…”
Section: Introductionmentioning
confidence: 93%
“…Yet it does provide an interesting approach for looking into early participation and recognition of the global structure of routines by focusing on the individual steps of the peekaboo game and how the infants fit their behavior into these. In concert with the evidence suggesting that sequential structure affects early participation in interactions (Fantasia et al, 2015 ), it seems plausible that mothers who create more opportunities for their infants to take up their turn will have infants who participate more actively than other infants.…”
Section: Introductionmentioning
confidence: 93%
“…But this physical weakness and inexperience, which needs for a long period of parental care, does not prevent the baby from attending intelligently to people and what they are doing. The baby moves to join in actions of a helper who is picking up and carrying them (Fantasia et al, 2016), or one who is offering objects with admiration for the baby's actions, and for the mind that guides them. In a few weeks the baby is starting to use vocal sounds as signs for marking special experiences in a 'line mode' of consciousness that can be about non-present things or happenings 'someplace, sometime' (Donaldson, 1992, p. 50).…”
mentioning
confidence: 99%
“…First, infants have also been observed to look longer at physically-possible-but-socially-unexpected events. For instance, Fantasia, Markova, Fasulo, Costall, & Reddy (2016) reported that 3-month-olds reacted with more frequent gaze shifts to a VOE. Mothers were instructed to reach for their babies and then stop with arms outstretched before actually picking up the baby.…”
Section: The Possibility Of Eventsmentioning
confidence: 99%
“…The mechanical and automated action seems to afford less possibility for rich emotional reactions by infants and indeed by adults. This automated or mechanical quality may in fact also characterize the actions of the mothers in the still face studies, or those instructed to reach for their infants without completing the action of picking them up, or to perform a normal game without sound as described above (Fantasia et al, 2014(Fantasia et al, , 2016Tronick et al, 1975), and thus lead to an inability to make sense of the event.…”
Section: Making Sense Of Incongruitymentioning
confidence: 99%